A NEW SPECIES OF ISCHAEMUM FROM SULAWESI - Marthen Theogives Lasut (BRIN Publishing (Penerbit BRIN), 2006)
LASUT, MARTHEN T. 2006. A new species of Ischaemum from Sulawesi. Reinwardtia 12(3): 257–259.––A new species of Ischaemum veldkampii Lasut sp. nov. is described.